2017
DOI: 10.3892/mmr.2017.8358
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of Wnt5a on the proliferation, differentiation and inflammatory response of keratinocytes

Abstract: The predominant role of Wnt family member 5A (Wnt5a) is to induce non-canonical Wnt signalling pathways, including the Wnt‑Ca2+ and Wnt‑planar cell polarity pathways. Enhanced Wnt5a expression is involved in the formation of psoriatic plaques; however, its mechanistic role remains to be determined. In the present study, the effects of Wnt5a expression on HaCaT keratinocytes were investigated. HaCaT cells were cultured in medium supplemented with 0, 40 or 80 ng/ml Wnt5a for 24 h. Cell proliferation, the cell cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“… 16 In HaCaT cells, after treatment with Wnt5a, the expression levels of inflammatory markers, including IFN-γ, IL-8 and IL-17A were unregulated. 17 IL-1α, TNF-α, IFN-γ, and TGF-α can induce the expression of Wnt5a. 5 All these inflammatory markers play critical roles in the pathogenesis and maintenance of psoriasis.…”
Section: Discussionmentioning
confidence: 98%
“… 16 In HaCaT cells, after treatment with Wnt5a, the expression levels of inflammatory markers, including IFN-γ, IL-8 and IL-17A were unregulated. 17 IL-1α, TNF-α, IFN-γ, and TGF-α can induce the expression of Wnt5a. 5 All these inflammatory markers play critical roles in the pathogenesis and maintenance of psoriasis.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies reported that several inflammatory cytokines could be upregulated, accompanied by G2/M phase arrest, by interfering with exogenous agents. 51 , 52 Therefore, we presumed that the expression of these inflammatory cytokines was elevated in the G2/M phase. Cell cycle synchronization of ccRCC cells was performed, and we detected their expression patterns in different phases.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, autocrine Wnt5a promotes the differentiation of NHEKs . In contrast, Wnt5a treatment can suppress HaCaT keratinocyte proliferation and differentiation, although the expression of IL‐8, IL‐17A and interferon‐γ was up‐regulated . It is difficult to interpret these somewhat contradictory results, but they indicate a complex and as yet unclear role of Wnt5a in modulating the proliferation and differentiation of keratinocytes.…”
Section: Proposed Mechanism Of Wnt5a Involvement In Psomentioning
confidence: 99%